AB0837 Circulating micrornas in systemic sclerosis patients reflect microrna profile of cultured scleroderma fibroblasts and correlate with distinct disease features. (23rd January 2014) - Vettori, S.; Maurer, B.; Iwamoto, N.; Filkova, M.; Cuomo, G.; Gay, R.E.; Valentini, G.; Gay, S.; Distler, O.
Abstract : Background: MicroRNAs (miRs) play a role in many pathophysiologic processes, and have been proposed as tissue-based biomarkers, which are released and stably detectable in body fluids. Objectives: To analyse serum expression of miRs which are down-regulated in cultured Systemic Sclerosis (SSc) skin fibroblasts and look for correlations with SSc patient's features. Methods: Pooled RNA from 3 SSc and 3 healthy control (HC) fibroblasts was used to screen the expression of 377 miRs by low-density array, and RNA from 12 individual SSc and 6 HC fibroblasts was used to confirm the results by Real time PCR. Serum was obtained from 40 SSc patients and 40 HCs. RNA was isolated by triple phenol-chloroform extraction, from 1 ml serum after adding a denaturing reagent and 62.5 fmol of synthetic cel-miR-39 to allow for normalization of total RNA among samples. A fixed volume of 1.67 μl RNA was used in each specific miR reverse transcription reaction. MiR expression was analysed by TaqMan Real-time PCR and dCt method using cel-miR-39 as control miR. Results: Nine out of the 26 miRs found to be down-regulated in SSc fibroblasts by low-density array were confirmed by Real-time PCR (miR-17-5p, miR-20a, miR-21, miR-24, miR-29a, miR-99a, miR-145, miR-186, and miR-193b; all p<0.05) and were investigated in serum samples. MiR-193b and miR-99a showed very low expression levels in HC sera and were not detectable in 20/40 and 12/40 SSc samples. MiR-17-5p was also not detectable in 12/40 SSc samples. Therefore, these miRs were excluded from further analysis. MiR-20a (p=0.003), miR-21 (p=0.002), miR-29a (p<0.0001), miR-145 (p=0.0001), and miR-186 (p=0.02) were down-regulated in serum from SSc patients as compared to HCs, whereas miR-24 showed no difference between the two groups. In SSc patients, levels of miR-29a and miR-186 were lower in patients with dcSSc subset (p=0.004; p=0.03), lung fibrosis (p=0.01; p=0.008), and FVC <80% (both p=0.001) on univariate analysis. In addition, both miRs negatively correlated with the modified Rodnan Skin Score (mRSS) (p=0.0002; p=0.006). MiR-21 levels were lower in patients with lcSSc subset (p=0.03), ACA positivity (0.002), digital ulcers (0.0004), and positively correlated with DLCO (p=0.02). MiR-20a levels were lower in patients with Scl-70 positivity (p=0.001) and free from digital ulcers (0.002), and negatively correlated with mRSS (p=0.02). MiR-145 levels did not show differences between disease subsets and patterns of organ involvement, but interestingly were affected by previous intake of cyclophosphamide (p=0.002). The association of low serum levels of miR-29a and miR-186 with FVC <80%, and the positive correlation of miR-20a with Scl-70 antibodies and the negative correlation with digital ulcers was confirmed on multivariate analysis. Conclusions: Most miRs down-regulated in cultured SSc fibroblasts are detectable in SSc serum samples and display a similar expression profile. Different miRs were associated with distinct SSc features at univariate analysis. Of note, miR-29a and miR-186 were independently associated to FVC <80% at multivariate analysis, and might be considered as candidate biomarkers for fibrotic lung involvement in SSc patients. Disclosure of Interest: S. Vettori Grant/Research support from: EULAR ODP, B. Maurer: None Declared, N. Iwamoto: None Declared, M. Filkova: None Declared, G. Cuomo: None Declared, R. Gay: None Declared, G. Valentini: None Declared, S. Gay: None Declared, O. Distler Grant/Research support from: EULAR ODP, Actelion, Pfizer, Ergonex, Sanofi, Consultant for: Actelion, Pfizer, Ergonex, BMS, Sanofi-Aventis, United BioSource Corporation, medac, 4D Science, Boehringer-Ingelheim, Active Biotech, Roche, Speakers Bureau: Actelion, Pfizer, Encysive, Ergonex